Study of fluid ingress through clear corneal incisions following phacoemulsification with or without the use of a hydrogel ocular bandage: a prospective comparative randomised study. (4th May 2014) - Sykakis, Evripidis; Karim, Rushmia; Kinsella, Matthew; Bhogal, Maninder; Patel, Sandeep; Parmar, Dipak N.
Abstract Purpose To assess the use of a hydrogel ocular bandage (HOB) on clear corneal incisions in phacoemulsification cataract surgery and determine whether HOB reduces ocular surface contaminants ingress after routine surgery. Methods In this prospective randomized controlled study, thirty eyes of patients undergoing uneventful phacoemulsification were recruited consecutively and randomly assigned to have a HOB applied to the corneal incision at the end of the surgery or not. At the end of the surgery, trypan blue (TRB) was instilled on the ocular surface, aqueous fluid was aspirated from the anterior chamber (AC) and its optical density was measured using ultraviolet spectrophotometry. The corneal incisions were examined postoperatively using anterior segment optical coherence tomography. Main outcome measures were concentration of TRB in the AC, corneal incision architecture, intraocular pressure (IOP) and Seidel test. Results All incisions were Seidel negative. The mean IOP in the immediate postoperative period was 18.1 ± 5.48 mmHg for the intervention group and 16.9 ± 5.7 mmHg for the control group (p > 0.05). No architectural differences of the incisions between the two groups were noted. The total mean length of the three‐step corneal incisions in the two groups was 2261.2 ± 96.92 μm and 2263 ± 119.75 μm, respectively (p > 0.05). No trace of TRB was detected in any of the samples. Conclusion Proper surgical wound construction without the use of a HOB is efficient in preventing the ingress of fluid through the main corneal incision postoperatively.